Environmental and economic impact of the use of natural gas for generating electricity in The Amazon: A case study (2015)
The transformations taking place in the Amazon, considered the "lungs of the planet", have special significance, not only for energy savings, but also for its environmental impact due to the reduction of greenhouse gases. Since 2010, in Manaus, the capital of Amazonas in Brazil, many power plants are replacing fuel oil with natural gas for power generation. Because of the large natural gas reserves in the region, this fuel has become the best choice for power plants built in this place. This paper analyzes the technical economic and environmental impact of the substitution of fuel oil by natural gas in the analyzed power generation plant.